Vitamin D Deficiency is Associated with Charcot Neuroarthropathy: A Case-Control Study. Issue 4 (November 2022) - Martinazzi, Brandon J.; Lorenz, F. Jeffrey; Nam, Hannah; Dopke, Kelly; Ptasinski, Anna; Mansfield, Kirsten N.; Kirchner, Gregory; Aynardi, Michael C.
Category: Diabetes; Trauma; Other Introduction/Purpose: Charcot Neuroarthropathy can be a challenging condition for the foot and ankle surgeon. Prior studies have reported Vitamin D deficiency to be associated with several lower extremity complications. However, the relationship between vitamin D deficiency and Charcot is not well defined. Therefore, the purpose of this study was to determine if patients with Charcot were more likely to be vitamin D deficient than patients with diabetes alone. Methods: A large online database from 2011-2021 was retrospectively queried using CTP and ICD codes. Patients were separated into two groups. Group A consisted of patients with diabetes and Charcot Neuroarthropathy. Group B consisted of patients with only diabetes. Statistical analysis was then run to determine if there was an association between Vitamin D deficiency in patients with Charcot compared to patients with diabetes alone. Demographics including age, sex, and race were also recorded. Results: From 2011-2021, a total of 5, 428, 806 were identified. Group A consisted of 13, 519 patients with a mean age of 59 +- 11.6 years. Of these patients, 60% were male (8, 064), 40% were female (5, 455), 72% were white (9, 725), 14% were Black or African American (1, 913), 1% were Asian (89), 13% were unknown (1, 730), <1% were American Indian (49), and <1% were Native Hawaiian (13). Group B consisted of 5, 415, 287 patients with a mean age of 59.6 +- 15.4. Of these patients, 50% were male (2, 693, 118), 50% were female (2, 720, 313), <1% were unknown (1, 856), 59% were white (3, 214, 4058), 19% were black or African American (995, 514), 3% were Asian (139, 732), 19% were unknown (1, 035, 894), <1% were American Indian (20, 681), and <1% were Native Hawaiian (13). Patients with Charcot were more likely to have Vitamin D deficiency than diabetic patients alone (OR: 1.687; 95% CI: 1.616, 1.761). Conclusion: In our cohort, patients with Charcot Neuroarthropathy were more likely to be Vitamin D deficient than patients with diabetes alone. Given that Vitamin D deficiency has been found to be associated with lower extremity complications, further investigation is warranted.